Poly (triazine imide) ligand based 2D metal coordination polymers: Design, synthesis and application in electrocatalytic water oxidation. (1st January 2022) - Sun, Jingwen; Dai, Liming; Yao, Fanglei; Zhao, Hongan; Bi, Jiabao; Xue, Wenkang; Deng, Jingyao; Fang, Chenchen; Fu, Yongsheng; Zhu, Junwu
Highlights: A series of 2D coordination polymers based on our firstly reported poly (triazine imide) ligand is fabricated via a bottom-up strategy . As-prepared Ni/Fe coordination polymers shows an ultrathin thickness of ∼5 nm and a desirable catalytic activity towards the OER. Mechanism investigations elaborate that the poly (triazine imide) ligand not only help to realize the 2D morphological generation, but also afford additive catalytic centers through creating the Lewis base sites, thus accelerating the oxygen species absorption and the reaction rate. ABSTRACT: 2D metal coordination polymers have emerged as a new serious of efficient electrocatalysts in OER for their abundant unsaturated coordination centers and high charge-carrier mobility. However, the synthetic routes are mostly depending on the top-down exfoliation with unavoidable structural fragmentation and the annoying sheets' re-stacking. Here, an electrocatalytic poly (triazine imide) ligand is firstly synthesized and successfully applied to construct the 2D Ni/Fe coordination polymers nanosheets (Ni/Fe-CPNs) through a bottom-up strategy. Average thickness of the nanosheets is around 5 nm, enabling the highly exposed reactive centers. Further benefiting from the ligand promotion effect, absorption of the oxygen species during the OER is effectively accelerated, thus improving the reaction kinetics. Accordingly, the Ni/Fe-CPNs reveals an adorable overpotential of 244 mV at the current density of 10 mA cm −2, and the Tafel value of 65.8 mv dec −1 . Both values are much better than that of commercial RuO2, and competitive to most of the reported catalysts. The ex-situ techniques, including Raman, FT-IR and XPS analysis alongside with applied potential, are also applied to elaborate the catalytic mechanism. This work offers a new point of view to improve the catalysts' activity. Graphical abstract: Image, graphical abstract